THE ROLE OF FUNCTIONAL MRI IN PRE-SURGICAL PLANNING FOR PATIENTS WITH EPILEPSY: REVIEW - Ibrahim Ahmed Maashi, ‏Merei Ibrahim Mohammed Ageel, Nasser Musawimabaroraybi, Mohammed Ahmed Hamedi, Ahmed Ali Maswadi, Hassan Rashed Ahmed Khormi, Mohammed Mousa Hassan Muyidi, Mazen Abdullah Mohammed Alqarni, Zubaida Najeeb Butaish,; Atallh Fawzan Almatrafi, Muhammad Abdul-Ghani, Muhammad Al-Maliki, Basil Ali Essa Alhadi, Sultan Abdilhadi Almalki, Elham Salman Alharthi (Chelonian Research Foundation, 2022)
No prior comprehensive analysis has been undertaken to examine all the available information on mapping eloquent cortex (namely motor, language, and memory areas) using modern functional neuroimaging techniques like as functional magnetic resonance imaging (fMRI) and magnetoencephalography (MEG) for children who are candidates for epilepsy surgery. The majority of research in this field has mostly focused on adult populations, and the effectiveness of these strategies in pediatric populations is not as well-established. A comprehensive study was conducted utilizing an advanced systematic search and retrieval method to analyze all published publications that investigate the use of functional neuroimaging in pediatric patients who are candidates for epilepsy surgery. Studies that have been obtained suggest that both fMRI and MEG are capable of providing evidence for the lateralization and localization of motor and linguistic functions. An important discovery from the analysis is the lack of research (n = 34) that specifically examine the demographic of children undergoing epilepsy surgery. The ideal activation produced by different language and memory paradigms in children is still uncertain, as well as how to accurately quantify it using rigorous statistical methods. Consensus must be reached for statistical analyses and the consistency and effectiveness of linguistic, motor, and memory paradigms. Extensive research are necessary to provide patient series data that doctors may use to objectively assess outcomes. In order for functional imaging methods to be a reliable option for mapping the eloquent cortex in children before surgery, it is necessary to create paradigms and studies that show agreement with independent measurements. Keywords: Paediatric, Epilepsy surgery, fMRI, MEG, Memory, Language, Motor